Pastoralism and early warning - Derbyshire, Samuel F. (International Livestock Research Institute, 2025)
'Lightning talk' presented by Sam Derbyshire (ILRI) at the Jameel Observatory Community of Practice meeting, Addis Ababa, 13-14 May 2025